John Manifold reading poetry in the Hazel de Berg collection - Manifold, J. S. (John Streeter), 1915-1985.; De Berg, Hazel, 1913-1984. (1959)
Manifold reads the following poems: "Brumby's run", "Bellerophon" and "The stranger".
Recorded by Hazel de Berg.
Digital master available
Uncorrected transcript (typescript, 1 leaf) available.
Keywords: Manifold, J. S. -- 1915-1985.; Australian poetry